EFEKTIVITAS METODE PERMAINAN BAHASA BISIK BERANTAI TERHADAP PENINGKATAN KETERAMPILAN MENYIMAK SISWA KELAS IV SD NEGERI 0501 HUTANOPAN - Era Mutiah (Prodi Pendidikan Guru Madrasah Ibtidaiyah STAIN Teungku Dirundeng Meulaboh, 2023)
Abstract Students' skills must be sharpened to see the rapid developments in today's era. Children's various skills must be developed, one of which is listening skills. If students' listening skills are not good then students' understanding of the material will also be poor. The aim of this research is to help improve students' listening skills through the whispering game method. The type of research used is Classroom Action Research (PTK) which consists of 2 cycles, each cycle consisting of planning, implementation, observation and reflection. This research data collection technique was obtained through observation, written tests and documentation. The data analysis technique in this research is a qualitative data analysis technique. Based on the research results, it can be concluded that using the chain whisper game method can improve students' listening skills, students become more active. In cycle I, 24 or 63.16% of students had the